'This Work In Hand My Friends May Have': Finding Female Ministers in Alternative Sources. Issue 2 (1st December 2022) - Rosner, Isabella
Abstract : This research note surveys findings about two early Quaker female ministers. A testimony written by the son of Gertrude Derix Niesen (unknown–1687) leads to a reconsideration of English–European relations at Waltham Abbey School, while a set of samplers stitched by Hannah Payton Young (1716–61), the sister of Catherine Payton Phillips (1727–94), allows us to reassess education within ministerial families. This article was published open access under a CC BY licence: https://creativecommons.org/licences/by/4.0 .